(untitled) (Homoeopathy for All, 2022)
As we all know increasing tension excessive use of mobiles ongoing disease such as deaths of loved ones; love betrayal; work-related stress, bullying and harassment, lone or remote working, violence in the workplace (both from staff and students), fatigue, alcohol and drug use; sedentary lifestyle; background radiations; segregate families and many more factors are continuously contributing to psychological hazards. These are leading to various common diseases such as anxiety disorders; mood disorders; sycotic diseases; dementia; eating disorders; ptsd; ocd’s; schizophrenia are the few of these innumerable diseases.